Diversidade cultural e políticas públicas educacionais : a proposta de Barão/RS : de 1930 a 1960 - Zanatta, Fernanda Rodrigues (My University, 2014)
The objective of this study is to analyze and debate the initiatives the deployment and conduct of educational processes in the town of Baron, in the period 1930 to 1960. The text provides for the identification and compares educational policies to the model already established in the region populated by immigrants by raising awareness of the issues surrounding culture and the meanings that they have on communities and the needs for cultural preservation, with the school as a support entity to preserve. Know and discuss the educational policies and practices carried out in schools, ethnic community and value the stories of communities, teaching units and regional cultures are goals listed in this research that is based on the concepts of representation and appropriation implicit in the initiatives and school practices of immigrants and community processes in place. Through the perspective of cultural history, analysis of documents and evidence provided interpretation and reconstruction of school a few times and spaces. The dissertation is organized into four chapters, the first of which presents considerations about the culture of a people, cultural diversity, cultural plurality. In the second chapter the area surveyed is presented in its historical arrival, organization and initiatives of immigrants, highlighting a second time initiatives and school practices. Following the text deepens the rules of nationalization of education to be made in the final chapter analyzes the crossovers and the school culture instituting and instituted. The school practices were strongly influenced the culture of immigrants, the language being the most striking aspect. The policies of a nationalist influenced and changed school practices and public school initiatives contributed to the closure of schools-ethnic community. Among the initiatives of the contributions of immigrants highlights the importance of education, education for the development of a people and a region.
O objetivo do presente estudo é conhecer e analisar o debate acerca das iniciativas de implantação e de condução dos processos educativos no município de Barão, no período de 1930 a 1960. O texto contempla a identificação e compara as políticas públicas educacionais ao modelo já estabelecido na região povoada por imigrantes sensibilizando para as questões que envolvem a cultura e os significados que estas têm para as comunidades, bem como para as necessidades da preservação cultural, tendo a escola como entidade de apoio para preservar. Conhecer e discutir as práticas e políticas educacionais realizadas nas escolas étnicocomunitárias e valorizar as histórias das comunidades, as unidades de ensino e as culturas regionais são objetivos elencados nesta pesquisa que tem como base os conceitos de representação e apropriação implícitos nas iniciativas e práticas escolares dos imigrantes e dos processos comunitários implantados. Através da perspectiva da História Cultural, a análise dos documentos e dos indícios proporcionou a interpretação e a reconstrução de alguns tempos e espaços escolares. A dissertação se organiza em quatro capítulos, sendo que o primeiro apresenta considerações a respeito da cultura de um povo, da diversidade cultural, da pluralidade cultural. No segundo capítulo a região pesquisada é apresentada em seus aspectos históricos de chegada, organização e iniciativas dos imigrantes, destacando num segundo momento as iniciativas e práticas escolares. Na sequência o texto aprofunda a legislação de nacionalização do ensino para que no capítulo final sejam feitos os entrecruzamentos e análises da cultura escolar instituínte e instituída. As práticas escolares apresentaram forte influencia da cultura dos imigrantes, sendo a língua o aspecto mais marcante. As politicas de cunho nacionalista influenciaram e modificaram as práticas escolares e as iniciativas escolares públicas contribuíram para o fechamento das escolas étnico-comunitárias. Dentre os contributos das iniciativas dos imigrantes destaca-se a importância do ensino, da escolarização para o desenvolvimento de um povo e de uma região.
Keywords: Multiculturalismo; Educação e Estado; Educação - História; Civilização - História; Cultural diversity